Emotional relationships between child patients and their mothers during dental treatments - Shizuka Tanaka; Naoko Uehara; Natsumi Tsuchihashi; Kumiko Sugimoto (Elsevier, 2016)
Background/purpose: The behavioral control of child patients is an important issue in pediatric dentistry. The emotional states of the mothers of patients may influence the attitudes of their children. The aim of this study was to investigate the emotional states estimated from physiological responses of child patients and the subjective anxieties of their mothers during dental treatments and discuss the emotional relationships between children and their mothers. Materials and methods: To assess physiological responses associated with emotional changes induced by dental treatments in child patients aged 3-6 years, activity in the autonomic nervous were analyzed from variations in inter-beat intervals in electrocardiogram. Anxiety levels of accompanying mothers were examined using the State Trait Anxiety Inventory, which was filled out during the treatment of their child. Results: Regarding the stress of child patients from the aspect of autonomic nervous activities during dental treatments, comparison between the cooperative and uncooperative patient groups showed that the uncooperative group demonstrated significantly higher sympathetic nervous activity and significantly lower parasympathetic nervous activity relative to the cooperative group, and their accompanying mothers showed significantly higher state anxiety scores relative to the mothers of cooperative children. Moreover, positive correlation between state anxiety scores of mothers and sympathetic nervous activities of their children was observed. Conclusion: These results indicated that uncooperative child patients undergo more stress and their mothers feel more anxiety from dental treatments, resulting in an emotional relationship between children and their mothers, which requires dental professionals to make special considerations to calm the anxiety of the mother, as well as the stress of the child patient.